1993
DOI: 10.1182/blood.v82.2.581.bloodjournal822581
|View full text |Cite
|
Sign up to set email alerts
|

Distinct ongoing Ig heavy chain rearrangement processes in childhood B- precursor acute lymphoblastic leukemia

Abstract: Acute lymphoblastic leukemia (ALL) is thought to arise from the clonal expansion of a single transformed precursor cell. However, an oligoclonal Ig heavy chain (IgH) rearrangement pattern has been observed in 30% of ALL patients and was shown to be the result of ongoing rearrangement events. The extent and nature of these ongoing rearrangement processes in individual patients has so far remained obscure. We performed a detailed analysis of leukemic VHDJH rearrangements in three children with B-precursor ALL at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Although both the v H 3 segment and the V62 segment had retained "cryptic" 3 heptamer sequences (see Fig. 5) that potentially allowed serial rearrangements to occur (Steenbergen et al, 1993), it seems unlikely that either of these two clones evolved from the other. For the inv( 14)(qllq32.3) to evolve into a V62-DS3 rearrangement, a re-inversion of chromosome 14 would be required.…”
Section: Discussionmentioning
confidence: 99%
“…Although both the v H 3 segment and the V62 segment had retained "cryptic" 3 heptamer sequences (see Fig. 5) that potentially allowed serial rearrangements to occur (Steenbergen et al, 1993), it seems unlikely that either of these two clones evolved from the other. For the inv( 14)(qllq32.3) to evolve into a V62-DS3 rearrangement, a re-inversion of chromosome 14 would be required.…”
Section: Discussionmentioning
confidence: 99%
“…Nadel et al 17 did not detect recombination in pre-B cells transfected with plasmids containing the complete nonamer-spacer-heptamer 'embedded RSS' present in the 3¢ end of several of the mouse V H genes, and concluded that V H replacement must be an infrequent event, unlikely to contribute significantly to receptor editing. However, numerous examples of V H replacement continued to be observed in pre-B-cell lines (endogenous genes and introduced substrates), lymphomas and leukaemias 15,[18][19][20][21][22][23][24][25][26][27][28][29] and in transgenic mice. 16,30,31 The reported Type 1 V H replacements fall into three subtypes.…”
Section: Type 1 V H Replacementmentioning
confidence: 99%
“…These AJO methods usually enable the detection of one residual clonal cell in 10 4 -10 6 normal cells (sensitivity level 10 ÿ 4 -10 ÿ 6 ), but are labour intensive and costly, thus limiting their application to large-scale clinical studies. In addition, clonal evolution, as evidenced by relapse with a clone demonstrating a different V-D-J junction, has been described in approximately 10-50% of IgH alleles (Baruchel et al, 1995;Beishuizen et al, 1994;Steenbergen et al, 1993), leading to false negative results with AJO probes. Alternative strategies, based either on the incorporation of 32 P-labelled nucleotides in the PCR step and analysis on high-resolution denaturing PAGE ('fingerprinting'), or the use of 32 P-labelled IgH CDR3 PCR product as a patient-specific probe, avoid the sequencing step and achieve a level of sensitivity of detection of 10 ÿ 3 -10 ÿ 4 Nizet et al, 1993).…”
mentioning
confidence: 99%